Edukasi Masyarakat Mengenai Adaptasi Kebiasaan Baru Guna Mencegah Penyebaran Virus COVID-19 Di Desa Penyak - Fitri Afriani; Yuant Tiandho (Fakultas Teknik, Universitas Bangka Belitung, 2021)
The COVID-19 pandemic that has spread to all countries has changed various human activities in the world. The new habitual adaptation policy is a policy taken by the Government of the Republic of Indonesia to prevent the spread of COVID-19 while still paying attention to the economic sector. Penyak Village is located in Koba District, Central Bangka Regency. As a village located adjacent to the sea, many residents in this village work as fishermen. Therefore, the new habit adaptation policy was welcomed by the community. To increase public understanding, the community service team provides education regarding the adaptation of new habits. The educational program is carried out through direct socialization and media such as posters and pocketbooks. Also, the educational program was followed by several activities such as spraying disinfectants, making handwashing facilities, blood donation, providing necessities to the community, and submitting educational media at the Penyak Village. Based on the evaluation using a questionnaire, more than 50% of the public stated that the educational media provided was of excellent quality and was influential in increasing understanding regarding the adaptation of new habits